Networks of phobic fear: Functional connectivity shifts in two subtypes of specific phobia. (1st January 2018) - Stefanescu, Maria R.; Endres, Ralph J.; Hilbert, Kevin; Wittchen, Hans-Ulrich; Lueken, Ulrike
Highlights: Phobic fear may be associated with connectivity in emotion-processing circuits. We found a positive coupling between para-limbic regions in phobia groups only. The observed negative connectivity in controls might represent fear inhibition. Stimulus modality may alter functional brain connectivity in dental phobia. Abstract: Anxiety disorders can be conceptualized by an abnormal interplay of emotion-processing brain circuits; however, knowledge of brain connectivity measures in specific phobia is still limited. To explore functional interactions within selected fear-circuitry structures (anterior cingulate cortex (ACC), amygdala, insula), we re-examined three task-based fMRI studies using a symptom provocation approach (n = 94 subjects in total) on two different phobia subtypes (animal subtype as represented by snake phobia (SP) and blood-injection-injury subtype as represented by dental phobia (DP)), and a non-phobic healthy control group (HC). Functional connectivity (FC) analyses detected a negative coupling between the amygdala and the ACC in HC for both classes of phobic stimuli, while SP and DP lacked this inhibitory relationship during visual stimulus presentation. However, a negative FC between the insula and the amygdala was observed in DP during visual symptom provocation, which reversed to a positive FC under auditory symptom provocation pointing to effects depending on stimulus modality in DP. SP showed significantly higher FC towards snake-anxiety eliciting stimuli than HC on an average measure of FC, while DP showed a similar pattern under auditory stimulation only. These findings altogether indicate FC shifts during symptom provocation in specific phobia possibly reflecting impaired emotion regulation processes within fear-circuitry networks. FC hence could represent a prime target for neuroscience-informed augmentation strategies when treating pathological forms of fear.